Engineering method for research of stress state in concentration areas of welded joints with symmetrical reinforcement - А. Moltasov; P. Tkach; S. Motrunich (Mechanics and Advanced Technologies)
Abstract. Subject, theme, aim. The subject of research in this work is the stress distribution in stress concentration areas of welded joints with double-sided symmetrical reinforcement. The topic of this work is related to development of engineering method of describing the stress state in the transition areas of weld to the base metal of butt and cruciform welded joints. The aim consists in establishing of mathematical relationships that describe the change of the first principal stress on the contour of the investigated area, and in the depth of the welded joint at tension and bending.